Foam fractionation for effective removal of Pseudomonas aeruginosa from water body: Strengthening foam drainage by artificially inducing foam evolution. (1st August 2021) - Jia, Lei; Liu, Wei; Cao, Jilin; Wu, Zhaoliang; Yang, Chunyan
Abstract: Lack of microbial contamination is of great significance to drinking water safety and water reclamation. In this work, foam fractionation was employed to remove Pseudomonas aeruginosa ( P. aeruginosa ) from aqueous solution and dodecyl dimethyl betaine (BS12) was used as the collector. Since the attachment of strain cells on the bubble surface would impede the reflux of interstitial liquid in the plateau borders (PBs), a novel strategy in strengthening foam drainage was developed through artificially inducing foam evolution. Two gas distributors with different pore diameters had been mounted at the bottom of the column for regulating the radial distribution of bubble size in the foam phase. Experimental results indicated that gas diffuse and bubble coarsening could be significantly promoted by increasing the size difference among the adjacent bubbles. Bubble coalescence contributed to broadening the width of plateau borders, thereby avoiding the borders blockage by strain cells. During bubble coalescence, surfactant molecules would be partially shifted from the surface of small bubble towards that of large bubble due to the molecule density difference. The increase in surface excess of surfactant molecules on gas-liquid interface was conducive to improving foam stability. Under the suitable conditions of air flow rates of gas distributor with 0.125 mm of pore diameter 75 mL/min and gas distributor with 0.425 mm of pore diameter 125 mL/min, BS12 concentration 0.1 g/L, and P. aeruginosa concentration 2.0 × 10 4  CFU/mL, the removal percentage and enrichment ratio of P. aeruginosa were 99.6% and 10.6, respectively. This work is expected to provide some new light for strengthening foam drainage in the presence of solid particles and to facilitate the industrialization of foam fractionation in water treatment. Graphical abstract: Image 1 Highlights: P. aeruginosa had been removed from aqueous solution by foam fractionation. Foam drainage was strengthened through regulating bubble size distribution. Foam permeability was increased by increasing the width of plateau borders. Bubble coalescence was conducive to reducing liquid holdup of the foam. The molecule transformation on bubble surface could enhance foam stability.